Combating money laundering and terrorist financing - the Nigerian experience (2016)
Money Laundering and Terrorist financing have become a serious problem facing the social, economic and political roots of Nigeria. Money Laundering is a process by which large amounts of illegally obtained money from drug trafficking, terrorist activity or other serious crimes, is given the appearance of having originated from a legitimate source. Terrorist financing is defined to include both legitimate and illegitimate money characterized by concealment of the origin or intended criminal use of the funds. The techniques used to launder money are essentially the same as those used to conceal the sources of, and uses for, terrorist financing. The activities of money launderers and terrorists are highly secretive and do not lend themselves to statistical analysis. These ugly monsters called terrorism and money laundering have adverse impact on the economy and political stability of a country and hence such an activity must be curbed with all seriousness. This paper discussed the concepts, significance and the impact of terrorist financing and money laundering in Nigerian economy. The paper observes that developing countries such as Nigeria and other member states of the ECOWAS and African Union AU face certain challenges in fully implementing the Financial Action Taskforce (FATF) recommendations because of lack of capacity and lack of financial resources amongst other reasons. Nations of the world must join hands and resources together in adopting measures aimed at dismantling syndicates engaged in money laundering by resorting to aggressive enforcement of anti-money laundering/ combating financing terrorism (AML/CFT) laws. It is, therefore, important that Nigeria establishes relationships with the international community so as to enhance intelligence gathering and sharing, law enforcement cooperation, economic sanctions, and in turn disrupt the flow of terrorist funding.